The text-critical and exegetical value of the Dead Sea Scrolls - Cook, Johann (HTS teologiese studies, 2016)
This article will analyse a number of Dead Sea manuscripts and/or fragments in order to determine their linguistic and exegetical value. The article will, firstly, address textual material that is largely in agreement with the Massoretic Text – 1QIsaa is a case in point. Secondly, fragmentsthat are seemingly less relevant will be discussed. The less helpful fragments from the Biblical books Proverbs and Job are taken as examples. Finally, highly significant textual differences, such as a fragment from Genesis 1 and one from the complicated books of Jeremiah, will be evaluated.